Inter-observer Agreement between Urologists and Radiologists in Interpreting the Computed Tomography Images of Emergency Patients with Renal Colic - Hong, Jun Young; Lee, Dong Hoon; Chang, In Ho; Park, Sung Bin; Kim, Chan Woong; Chi, Byung Hoon (Urology Journal, 2018)
Purpose: Low-dose non-enhanced computed tomography (LDCT) has been shown to provide low radiation exposure with proper diagnostic accuracy compared to standard dose non-enhanced computed tomography (SDCT) in patients with renal colic. The goal of our study is to estimate the accuracy of LDCT and SDCT interpretation by emergency medicine residents who primarily treated patients with renal colic. Materials and Methods: Thirty sample images of both LDCT and SDCT from renal colic patients were extracted from January 2013 to December 2015 in a tertiary teaching hospital. Five emergency medicine residents interpreted 60 image samples over a time span of 3 weeks. The presence of a ureteric stone, the stone’s size and location, and signs of obstruction were recorded in the reports. A total of 300 reports were compared with formal readings by a radiologist. The inter-observer agreement and kappa value were calculated for comparative analysis. Results: Identification of ureteric stones showed almost perfect inter-observer agreement on SDCT (kappa value: 0.93), and the percentage of agreement was 96.7%. However, on LDCT, the inter-observer agreement was substantial (kappa value: 0.73), and the percentage of agreement was 88.0%. Conclusion: Using SDCT, emergency medicine residents had almost perfect inter-observer agreement in interpreting the CT images of patients with renal colic compared to a radiologist. However, when using LDCT, they had a lower inter-observer agreement.